Folk performing arts of Southern Karnataka Part-4 - (:unkn) unknown (My University, 2023)
Folk dance is a medium of expression of a primitive man aspiration in life.Here goes a saying like this: life without art is like an ocean without a wave. It means there is a close intimate relationship between art, human being and society. Though ocean looks calm and spread. It makes us joyous through it waves. So also art in human life. So it adds joy,happiness through it waves. So also art in human life.So it adds joy,happiness and colour to human life. Goravara Kunitha are remembered for the unique performance to singing, costume and the perhegya. Dancing in a variety of step and costume with differently designs and along by them they used the plain ground to perform.They travel place to place placing people and children and removing there filth from body and mind. The Gorava dance is greatest folk dance in Karnataka. It belongs to the tradition of folk singer. The Gorava tradition belongs to Shaiva cult. They express both the human and animal instinct.In the Southern part of Karnataka they are known by Gorava, Goggaiya, Gaddabaddaiya. Whereas in the northern part they called as gwarappa,Vagga,Vaggayya.The Gorava Dance and the Dollu dance are the two great contributions that were given to the people of Karnataka by the Shephard Communities. The term Gorava has originated from the Goravayya or Guru meaning the teacher. This dance is performed during the ritualized, Customary Practices, festival and religious procession. In northern Karnataka the Gorava dance is known as Kadabadayyan Kunitha. The Instrument the Goravas use is called as Kadabadi whereas the same instrument in south is called as damaruga or Dindima. Gaarudigombe Kunitha doll dance is also known as Tottirayana or Manu Bombalu. This dance is spread in Mandya,Mysore,Shimoga,Tumkur,Kolar and Banglore rural district.The Performers is mainely intended to entertain people. Garudi Gombe Kunitha is an entertaining folk dance.There are male and female figures/Dolls.The male doll that dances is as tall as fifteen feet. The female doll holds the waist while dancing. These doll dances are particularly invited during public processions and functions to perform. The Garudi Dance is hailed as belonging to Vaishnava tradition. It makes the onlooker to fall in love with the Garudi Gombe. Earlier times these dolls used to dance in village festivals to perform. Thus it symbolizes the cultural heritage to Karnataka. Patada kunitha,while the Nandi flag belong to Shiva tradition the Patada dance represents the art of Vaishanava tradition. Mandya,Tumkur,Mysore and Bengluru Rural district is house the Patada Kunitha. It resemble the Rangad Kunitha. Fifteen to twenty feet bomboo stick is decorated with colourful clips and silk tassel. The folk dance of Patada kunitha was born out of the Patada Kunitha was born out of the Melukote temple. Here there is another form called Bhagavanthike mela. In the Goparu kunitha dancer holds the patasa in tower shape and dance in circular form.
Keywords: Folk performing arts of Southern Karnataka; Southern part- Gorava; Goggayya; Gadbaddayya; Gaarudigombe kunitha; Patada kunitha; Kannada